Formulación del Plan de Gestión Integral de Residuos Sólidos en el conjunto residencial La Alejandra I Etapa (2020)
The residential complex La Alejandra I stage, is a space in which day by day large amount of solid waste of different types is generated and these are not managed as it should be, that is why the proposal for the PGIRS is something of paramount importance, in order to avoid damage to human health, to the environment, possible offensive odors and presence of unwanted vectors. 1 For the realization of the plan of integral management of solid waste in the set were taken into account four phases, the first phase was the diagnosis, in which the location of the site of study was determined, and some necessary characteristics. The second phase focused on identifying the waste, its sources of generation, and its current storage site. The third phase was that of qualitative and quantitative measurement, in which the characterization was carried out by means of the quarto, and their respective calculations, this in order to know in what way the residues behave in the set The Alexandra I. And the fourth and last phase, was the program for pgirs, in which the problems encountered were taken into account, in order to arrive at a possible solution.